The determinant household debt in Asia Pacific / Farah Amizah Mohd Amin - Mohd Amin, Farah Amizah (Faculty of Business and Management, 2018)
Household debt problem is established to have initiated economic slowdown and financial crisis resulting in unsustainable global financial stability. High level of household debt may be result in emotional and psychological stress as well as social and family predicament in the domestic economy. This research analyze about the determinants of household debt in Asia Pacific countries from year 2006 to 2015. There are six determinants relate to household debts which are Gross Domestic Product (1), Consumption (2), Savings (3), interest rate (4), unemployment rate (5) and lastly house price index (6). Simple Random regression model were carried out to study the relationship between dependent variable which is household debt and independent variable which are Gross Domestic Product (1), Consumption (2), Savings (3), interest rate (4), unemployment rate (5) and lastly house price index (6). Empirical result shows the positive and significant relationship between household debt with Gross Domestic Product and household consumption and significant negative relationship with independent variable like saving, interest rate and unemployment. Empirical result also shows there was insignificant relationship between household debt and house price index.